A municipalização portuária em Itajaí e a redefinição das relações entre cidade e porto - João Grand Junior (Confins)
The crisis of fordism at the end of the last century undermines the strategies and classic mechanisms for the management of material and immaterial flows produced in an increasingly globalized economy. Some authors consider that this could be the emergence of a period dominated by the logistics and integrated management of the production process – where productivity is more closely linked to the ability of organization, coordination and interaction among the various segments and actors, promoting what Veltz (1999) called “competitiveness through differentiation” – rather than the logics of the transports and segmented production of Taylorism type. Based on this scenario, new prospects of integration into world economy are drawn from various strategies of the more economically competitive regions and the others. The global economic space acquires a new configuration and redefines the contours of the international territorial division of labour. Under these transformations, territorial disputes occur in all geographic scales to “capture” the investments and flows of globalization. In this context, the city-ports becomes a economic space with great potential for organizing the world economy. They are positioned as strategic nodes in the economy-networks that attract/articulate the material and immaterial flows that multiply in contemporary capitalism. Thus, based on a systemic and territorial approach, we intend to analyze the productive dimension of the relation between city and port that is configured in the city of Itajaí, Santa Catarina, from the municipalization of the port in mid 1990s. In addition to its pioneering use of the regulatory device that allows the transfer of responsibility for administration of the ports of the Union for municipalities; Itajaí also figures as a unique case of integrated management between city and port. This experience allows the constitution of a port tertiary in the region and increases its competitiveness in the global marine system port.